Answer :
Answer:
(13, - 10 )
Step-by-step explanation:
Given the endpoints (x₁, y₁ ) and (x₂, y₂ ) then the midpoint is
[ [tex]\frac{1}{2}[/tex](x₁ + x₂ ), [tex]\frac{1}{2}[/tex](y₁ + y₂ ) ]
let endpoint 2 = (x, y ), then equate to the coordinates of midpoint, that is
[tex]\frac{1}{2}[/tex] (- 9 + x ) = 2 ( multiply both sides by 2 )
- 9 + x = 4 ( add 9 to both sides )
x = 13
[tex]\frac{1}{2}[/tex] (8 + y) = - 1 ( multiply both sides by 2 )
8 + y = - 2 ( subtract 8 from both sides )
y = - 10 )
endpoint 2 = (13, - 10 )